The Influence of Perceived Waiting Time and Medication Information on Word of Mouth Mediated by Patient Satisfaction - Rozet, Stefly Julisye Amerence; Patiro, Shine Pintor Siolemba; Mindarti, Ceacilia Sri; Rekarti, Endi; Yusriani, Sri; Muzhaffar, Haydar Zharif (Yayasan Sinergi Kawula Muda, 2024)
This paper examines the impact of perceived waiting time and the delivery of medication information on word of mouth, mediated by patient satisfaction, at RSUD Beriman Balikpapan. Improving pharmaceutical services, including reducing waiting times and enhancing information delivery, is crucial for patient satisfaction and hospital reputation. This study investigates whether patients' perceptions of waiting times and medication information delivery affect their satisfaction and subsequently their likelihood to engage in word of mouth promotion. This research addresses the gap in understanding how specific aspects of pharmaceutical service quality influence word of mouth through patient satisfaction, a topic not extensively studied in the context of Indonesian public hospitals. A quantitative approach was employed, using primary data from questionnaires distributed to 130 outpatients at RSUD Beriman Balikpapan. Purposive sampling was used, and the data were analyzed using variance-based SEM (PLS) with SMART PLS 3.0. The analysis revealed that perceived waiting time and medication information delivery significantly and positively influence word of mouth, mediated by patient satisfaction. All five hypotheses were supported, with t-statistic values exceeding 1.96 and p-values below 0.05. The study concludes that improving perceived waiting time and medication information delivery enhances patient satisfaction, leading to increased word of mouth promotion. This suggests that hospitals should focus on these aspects to improve overall service quality and patient advocacy.